A meeting and a mandate: CTA is on the move - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Readers of Spore will no doubt recall that CTA was established almost two decades ago under the second Lomé Convention between the African, Caribbean and Pacific Group of States and the Member States of the European Community. The signing of a new...